Professor Abraham Akerman - Helio Afonso Ghizoni Teive; Francis Paciornik Zorzetto; Adriana Moro; Renato Puppi Munhoz; Pericles Andrade Maranhao Filho; Edison Matos Novak (Arquivos de Neuro-Psiquiatria)
The authors present a historical review of the contribution of Professor Abraham Akerman to Brazilian neurology, including the famous sign known as “the Alajouanine-Akerman unstable ataxic hand”.